TERT rs2853676 polymorphisms correlate with glioma prognosis in Chinese population - He, Xue (Oncotarget, 2016)
High rates of recurrence and the lack of effective treatments contribute to the poor prognosis of patients with glioma. There is therefore an urgent need for an easily detectable biomarker to facilitate early detection. In this study, we explored the association between TERT rs2853676 genetic polymorphisms and the prognosis of Chinese glioma patients. A total of 481 glioma patients at the Tangdu Hospital of the Fourth Military Medical University in China were included in this study. The overall survival rates were calculated using the Kaplan-Meier method. Prognostic factors were determined through multivariate Cox regression analysis. The overall survival (OS) rates of one, two, and three years were 31%, 10.3%, and 7.5%, respectively. The progress-free survival (PFS) rates of one, two, and three years were 15.7%, 7.3%, and 4.7%, respectively. The genotype “A/G” of TERT rs2857676 decreased the PFS rate (hazard ratios [HR] = 0.824; P = 0.059). The genotype “A/G (HR = 0.803; 95% CI, 0.656 – 0.982; P = 0.032)” and “A/A + A/G” decreased the recurrence rate compared to the genotype G/G (HR = 0.818; 95% CI, 0.675-0.99; P = 0.040). Our study indicates that TERT rs2853676 polymorphisms correlate with glioma survival and recurrence rates in a Chinese population, which suggests that they could potentially serve as prognostic markers in glioma patients.